Simplify the expression:
2a − 4b + 7 + 8a + 6b − 2
Combine like terms (a's and b's separately):
(2a + 8a) + (-4b + 6b) + (7 - 2)
Simplify each set of like terms:
10a + 2b + 5.
Simplify 2a − 4b +7 + 8a + 6b − 2.(1 point)
3 answers
Simplify 6/7c − 5/9d − 1/2 c + 1/3d.(1 point)
To simplify the expression, we need to combine like terms with the same variable.
To do this, we will first combine the terms with c: 6/7c - 1/2c.
When we combine the fractions, we need a common denominator, which in this case is 14.
6/7c * (2/2) - 1/2c * (7/7)
= 12/14c - 7/14c
= (12 - 7) / 14c
= 5/14c
Next, we will combine the terms with d: -5/9d + 1/3d.
To combine the fractions, we need a common denominator, which in this case is 9.
-5/9d * (1/1) + 1/3d * (3/3)
= -5/9d + 3/9d
= (-5 + 3) / 9d
= -2/9d
Therefore, the simplified expression is:
5/14c - 2/9d
To do this, we will first combine the terms with c: 6/7c - 1/2c.
When we combine the fractions, we need a common denominator, which in this case is 14.
6/7c * (2/2) - 1/2c * (7/7)
= 12/14c - 7/14c
= (12 - 7) / 14c
= 5/14c
Next, we will combine the terms with d: -5/9d + 1/3d.
To combine the fractions, we need a common denominator, which in this case is 9.
-5/9d * (1/1) + 1/3d * (3/3)
= -5/9d + 3/9d
= (-5 + 3) / 9d
= -2/9d
Therefore, the simplified expression is:
5/14c - 2/9d